A Study on the Burn Pattern Experiments in Structure Fire - Song, Gi-Dong; Hur, Man-Sung; Lee, Hyun-Joo (Proceedings of Engineering and Technology Innovation, 2017)
The fire has created tremendous damage, yet skilled fire investigators can read the fire patterns left by the fire. Through the fire patterns interpretation and analysis, fire investigators should be able to determine exactly how and where the fire or explosion started. Fire patterns can help the fire investigator trace fire movement back to the point of origin. The origin and cause investigation for is attempting to determine the first material ignited, the source of ignition, and how the two brought together to cause the ignition. The investigators should read the fire scene to establish the area of origin. In this study, through burn pattern experiments, fire behavior in the compartment, fire pattern formation mechanism, fire patterns reproducibility, fire patterns persistence through flashover and full room involvement condition, fire scene reconstruction for fire origin determination, and other fire pattern’s temperature will be discussed and analyzed in depth. Burn test was conducted to recognize and analyze fire patterns created in the phase of pre flashover or post flashover in the compartment (container house). In addition, fire pattern experiments are designed to test combustible material, including polyurethane foam with a lower thermal inertia or wooden chair with a higher thermal inertia. During these experiments, through the thermocouple fire pattern’s temperature will be measured in the stage of pre flashover or post flashover.